Adult Attachment Style to Online Surveillance: The Role of Investment and Commitment in Young Adults’ Romantic Relationships - Amanda, Aliyya; Ratnasari, Yudiana (Psikostudia : Jurnal Psikologi, 2025)
Social media plays a significant role in the dynamics of romantic relationships, including the emergence of online surveillance, which refers to the act of monitoring a partner’s activity on social media. This study aims to examine the mediating roles of investment and commitment in the relationship between adult attachment style and online surveillance among 175 young adult participants currently in dating relationships. A quantitative serial mediation approach was employed. The instruments used include the Experiences in Close Relationship–Short Form (ECR-SF), the Investment Model Scale (IMS), and the Interpersonal Electronic Surveillance Scale (IESS). The results of the serial mediation analysis showed no significant mediating role of investment and commitment in the relationship between adult attachment style and online surveillance for both anxious and avoidant attachment styles. Gender was included as covariates. However, additional analysis revealed that investment functioned as a significant single mediator in the relationship between both anxious and avoidant attachment styles and online surveillance. Commitment, on the other hand, did not serve as a significant mediator. These findings indicate that online surveillance behavior is more influenced by the level of emotional investment in the relationship.Media sosial berperan penting dalam dinamika hubungan romantis, salah satunya memunculkan perilaku online surveillance atau memantau aktivitas daring media sosial pasangannya. Penelitian ini bertujuan untuk menguji peran investasi dan komitmen sebagai mediator dalam hubungan antara adult attachment style dan online surveillance pada 175 partisipan usia dewasa muda yang sedang menjalin hubungan pacaran dengan pendekatan kuantitatif mediasi serial. Alat ukur yang digunakan mencakup Experiences in Close Relationship–Short Form (ECR-SF), Investment Model Scale (IMS), dan Interpersonal Electronic Surveillance Scale (IESS). Hasil analisis mediasi serial menunjukkan bahwa tidak terdapat peranan investasi dan komitmen yang signifikan sebagai mediator dalam hubungan antara adult attachment style terhadap online surveillance, baik anxious maupun avoidant attachment dengan jenis kelamin sebagai kovariat. Hasil analisis tambahan menunjukkan peran investasi yang signifikan sebagai mediator tunggal dalam hubungan antara anxious dan avoidant attachment style terhadap online surveillance, serta tidak ada peran komitmen yang signifikan sebagai mediator. Temuan ini menunjukkan bahwa perilaku online surveillance lebih dipengaruhi oleh besarnya investasi dalam hubungan.